A mathematical pandoras box - Bolt,Brain (New Delhi : Cambridges, 2005)
A Mathematical Pandora's Box has been written in response to the success of Brian Bolt's earlier mathematical puzzle books. Through his own experience, the author has discovered a worldwide interest in these and similar puzzles. Not only do they stimulate creative thinking but they can also open up new areas of mathematics to the reader. This book contains 142 activities: in addition to puzzles, there are games, tricks, models and explanations of various phenomena. They range from number manipulation, through happy and amicable numbers, coin puzzles, picnicking bears and pentominoes, to building shapes with cubes. Some of the puzzles date from hundreds of years ago while many others are original, giving everyone something to think about. There is a detailed commentary at the end of the book, giving solutions and explanations, together with the occasional follow-up problem
Keywords: Mathematical recreations. -- Recreations & Games